Pemberdayaan Ekonomi Kreatif Masyarakat Desa Haurwangi melalui Pelatihan Pengolahan Minuman Lokal - Ridwan Iskandar; Retno Budi Wahyuni; Nandang Suhada Yasir Mansyur; Moch. Agus Syadad Saefullah; Odang Rusmana (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2025)
The Pokland ecotourism area in Haurwangi Village possesses natural potential that has not been optimally harnessed by community economic empowerment. The local community has not yet been able to optimize local ingredients into products with economic value, resulting in limited participation and benefits from the tourism sector. This community service activity aims to empower the community through training in processing locally sourced beverages, creating new business opportunities and increasing economic value. This study employed a mixed-methods approach with a participatory action research design. Fifteen participants participated in the intensive training. Quantitative data were collected through pre- and post-test questionnaires, analyzed using paired sample t-tests. Qualitative data obtained from observations and in-depth interviews were analyzed thematically. The analysis showed a significant increase in participants' knowledge and skills, namely 76,32%. Not only cognitive and psychomotor aspects were affected, but psychological empowerment also occurred in the form of increased self-efficacy and a shift in mindset toward local ingredients. The formation of business groups and the commitment of ecotourism managers to integrate these products are strong indicators of the program's sustainability. Integrated training with the market has proven effective as a sustainable empowerment model. Collaboration between the community as producers and destination managers as distributors is key to the model's success.